Post-Gender-Based Violence Services Utilization Among Female Entertainment Workers in Cambodia: A Cross-Sectional Study - Oy, Sreymom (Violence against women, 2024)
Little is known about service utilization among female entertainment workers (FEWs) after experiencing gender-based violence (GBV). This study explored factors associated with post-GBV service utilization among FEWs in Cambodia. We included 299 FEWs, who experienced any forms of GBV in the past 12 months. This study highlights low access (14.05%) to post-GBV services among FEWs. Factors associated with post-GBV services utilization were marital status, living conditions, mental health, and types of entertainment venues. To improve post-GBV services utilization, ensuring quality, and availability of services are required. Further research is needed to develop pathways toward a supportive environment for FEWs to access these services.